A nuclear role for the Fragile X mental retardation protein. - Fridell, R A (1996)
Fragile X syndrome results from lack of expression of a functional form of Fragile X mental retardation protein (FMRP), a cytoplasmic RNA-binding protein of uncertain function. Here, we report that FMRP contains a nuclear export signal (NES) that is similar to the NES recently identified in the Rev regulatory protein of human immunodeficiency virus type 1 (HIV-1). Mutation of this FMRP NES results in mis-localization of FMRP to the cell nucleus. The FMRP NES is encoded within exon 14 of the FMR1 gene, thus explaining the aberrant nuclear localization of a natural isoform of FMRP that lacks this exon. The NES of FMRP can substitute fully for the Rev NES in mediating Rev-dependent nuclear RNA export and specifically binds a nucleoporin-like cellular cofactor that has been shown to mediate Rev NES function. Together, these findings demonstrate that the normal function of FMRP involves entry into the nucleus followed by export via a pathway that is identical to the one utilized by HIV-1 Rev. In addition, these data raise the possibility that FMRP could play a role in mediating the nuclear export of its currently undefined cellular RNA target(s).